Influencework Discipline and Work Environment on Employee Performance With Job Satisfaction as an Intervening Variable at the Padang City Education and Culture Office - Vina Yuniarti; John Veri (Sean Institute, 2025)
This study aims to examine how much influence e-attendance, organizational commitment and additional employee income (TPP) have on employee performance with job satisfaction as an intervening variable at the Community and Village Empowerment Service in Sungai Penuh City. The data collection method was through surveys and distributing questionnaires, with a sample of 73 respondents. The analysis method used structural equation modeling using smartpls. The results of the study showed an insignificant effect of e-attendance on job satisfaction at the Community and Village Empowerment Service in Sungai Penuh City. There is a significant effect of organizational commitment on job satisfaction at the Community and Village Empowerment Service in Sungai Penuh City. There is a significant effect of additional employee income (TPP) on job satisfaction at the Community and Village Empowerment Service in Sungai Penuh City. There is an insignificant effect of e-attendance on employee performance at the Community and Village Empowerment Service in Sungai Penuh City. There is an insignificant effect of organizational commitment on employee performance at the Community and Village Empowerment Service in Sungai Penuh City. There is an insignificant effect of additional employee income (TPP) on employee performance at the Community and Village Empowerment Service of Sungai Penuh City. There is a significant effect of job satisfaction on employee performance at the Community and Village Empowerment Service of Sungai Penuh City. Job satisfaction does not mediate the effect of e-attendance on employee performance at the Community and Village Empowerment Service of Sungai Penuh City. Job satisfaction mediates the effect of organizational commitment on employee performance at the Community and Village Empowerment Service of Sungai Penuh City. Job satisfaction mediates the effect of additional employee income (TPP) on employee performance at the Community and Village Empowerment Service of Sungai Penuh City.